Peptide selection via phage display to inhibit Leishmania-macrophage interactions - Verga, Juliane Buzzon Meneghesso; Graminha, Márcia A. S.; Jacobs-Lorena, Marcelo; Cha, Sung-Jae (Frontiers in Microbiology, 2024)
Introduction Leishmaniasis comprises a complex group of diseases caused by protozoan parasites from the Leishmania genus, presenting a significant threat to human health. Infection starts by the release into the skin of metacyclic promastigote (MP) form of the parasite by an infected sand fly. Soon after their release, the MPs enter a phagocytic host cell. This study focuses on finding peptides that can inhibit MP-phagocytic host cell interaction. Methods We used a phage display library to screen for peptides that bind to the surface of L. amazonensis (causative agent for cutaneous leishmaniasis) and L. infantum (causative agent for cutaneous and visceral leishmaniasis) MPs. Candidate peptide binding to the MP surface and inhibition of parasite-host cell interaction were tested in vitro. Peptide Inhibition of visceral leishmaniasis development was assessed in BALB/c mice. Results The selected L. amazonensis binding peptide (La1) and the L. infantum binding peptide (Li1) inhibited 44% of parasite internalization into THP-1 macrophage-like cells in vitro. While inhibition of internalization by La1 was specific to L. amazonensis, Li1 was effective in inhibiting internalization of both parasite species. Importantly, Li1 inhibited L. infantum spleen and liver infection of BALB/c mice by 84%. Conclusion We identified one peptide that specifically inhibits L. amazonensis MP infection of host cells and another that inhibits both, L. amazonensis and L. infantum, MP infection. Our findings suggest a promising path for the development of new treatments and prevention of leishmaniasis.